Kinematics Analysis of a 3DoF Lower Limb Exoskeleton for Gait Rehabilitation: A Preliminary Investigation - Muhammad Aizzat, Zakaria; Anwar, P. P. A. Majeed; Ismail, Mohd Khairuddin; Zahari, Taha (Springer, 2017)
Robotics have been engaged to address the shortcomings of conventional rehabilitation therapy as well as the ever increasing demand for rehabilitation services. This paper presents the kinematics of a 3DoF lower limb exoskeleton restricted to the sagittal plane. The Denavit-Hartenberg representation, as well as the geometrical solution approach, are employed to obtain the forward and inverse kinematics of the exoskeleton, respectively. A simulation study is performed to validate the proposed model.